RELIGIUSITAS SOLUSI KENAKALAN PADA REMAJA: (Kajian Islam dan Psikologi pada remaja) - Ainul Yaqin, Firdaus (LP3M UNZAH GENGGONG, 2019)
Abstract The level of crime committed by adolescents is very worrying, from brawls between students to motorcycle gangs. The existence of adolescents who should be the hope of the future becomes a kind of public enemy. Bad stigma is often pinned for adolescents who generally like group activities. This is not without reason, because it is often the case of crimes committed by adolescents. Of course this is very sad, teenagers who are the vanguard in the progress of the nation even slowly make the nation run without hope. There are several factors that cause adolescents to commit irregularities and even criminal acts, including the factor of the absence of calm in their souls. The absence of calm is caused by two things. First, for adolescents who already have religious knowledge, feel that their knowledge is not able to answer the anxiety that is in them, religious teachings that they previously believed felt less convincing, so they ask critical questions about things they previously believed, when they get answers those who are able to calm them will be more religious, but if not, they will leave the teachings. second, for adolescents who do not have religious knowledge, they feel ashamed because they have to learn from the beginning so they are reluctant to study religion. For this reason, a different model is needed to teach religion to adolescents so that religious teachings are able to become a part of their lives so that they are more religious and in the end it is expected that with religiosity, deviations by adolescents can be reduced. Keyword: religiosity, youth and religion